A class of completely regular spaces - Patrik E. Eklund (International Journal of Mathematics and Mathematical Sciences)
In this paper we investigate topologies with ultrafilters having bases of open sets. It is shown that these topologies are completely regular. All results are obtained by using Richardson's compactification of convergence spaces. We also prove a non-existance of a dense convergence space compactification with lifting property.